Manajemen Pemasaran Global Dalam Meningkatkan Kepuasan Konsumen dan Keberhasilan Bisnis - Ratu Hedy Syahidah Budiarti (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
In the era of globalization that we are currently experiencing, all aspects of human life are interconnected and related to one another. This indicates that it is no longer possible to understand the complexity of various economic, political and cultural relationships from just one particular point of view or perspective. Globalization has changed the way we live our daily lives, work and consume in almost all corners of the world. The phenomenon that emerged as a result of globalization is modernization, which can be defined as a process in which society increasingly relies on technology to meet their various needs and demands. In the business world, technology has become one of the most vital elements, especially in the context of social marketing, and more specifically, global marketing. Therefore, the aim of this research is to investigate and understand the role of global marketing management in increasing consumer satisfaction. By understanding how global marketing management can play a role in meeting the needs and expectations of consumers in Indonesia, you can gain valuable insight into how companies can adapt and succeed in an ever-changing global market.